PENGARUH KETERSEDIAAN FASILITAS, MODEL PEMBELAJARAN, DAN KOMPETENSI DOSEN TERHADAP PEMAHAMAN MAHASISWA TENTANG MANAJEMEN PERKANTORAN DI POLITEKNIK NEGERI AMBON - Victorio Fernando Nahumay (Jurnal Administrasi Terapan, 2023)
This study aims to analyze the influence of Facility Availability (X1), Lecturer Competence (X2), and Learning Models (X3) on Students' Understanding of the Office Management course at Ambon State Polytechnic. The research population includes all students of the Department of Business Administration who have taken or are currently taking the Office Management course. A total of 100 individuals were selected as the sample for this study. Data collection was carried out using a questionnaire based on a Likert Scale with five alternative responses. The collected data was processed using Ms. Excel 2010 and SPSS 22 and analyzed through descriptive analysis and multiple regression analysis. The results of the analysis show that Facility Availability (X1), Lecturer Competence (X2), and Learning Models (X3) have a positive and significant influence, both partially and simultaneously, on students' understanding of Office Management (Y). Therefore, it is recommended that Ambon State Polytechnic increase investment in educational infrastructure, including comfortable classrooms, computer laboratories with the latest software, fast internet access, and more comprehensive library resources. Efforts should be made to develop lecturer competencies through training and teaching development. The implementation of innovative learning models through the adoption of interactive learning models should also be carried out. Continuous monitoring and evaluation of the effectiveness of facilities, lecturer competence, and the learning models used, as well as enhancing collaboration with external parties, are also recommended.Keywords: Facilities, Lecturer Competence, Learning Models, Students' Understanding